Obtaining Learning Outcomes through Skill Based Interventions - Chandiraleka, G. (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Quality education is about attaining learning outcomes and life learning for all. Quality improvement in education is a holistic development of learners. In order to ensure quality education in primary level, new pedagogies should be implemented in our education system. The new teaching methodology should also ensure that learning process happens throughout the life. In primary level, children are very curious in doing activities. They are more interested in doing activities than classroom teaching. The children feel bored in normal chalk and talk method. So, the researcher uses the new technique to engage them in learning process actively. It also helps to obtain the expected learning outcomes without burdening the children.